2006
DOI: 10.1088/1742-5468/2006/06/p06016
|View full text |Cite
|
Sign up to set email alerts
|

Critical ageing of Ising ferromagnets relaxing from an ordered state

Abstract: We investigate the nonequilibrium behavior of the d-dimensional Ising model with purely dissipative dynamics during its critical relaxation from a magnetized initial configuration. The universal scaling forms of the two-time response and correlation functions of the magnetization are derived within the field-theoretical approach and the associated scaling functions are computed up to first order in the ǫ-expansion (ǫ = 4 − d). Aging behavior is clearly displayed and the associated universal fluctuation-dissipa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
145
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(162 citation statements)
references
References 64 publications
11
145
0
6
Order By: Relevance
“…As explained in subsection 2.1, Ξ −1 = 0 is a signal of the breaking of the RR symmetry characterizing the non-equilibrium stationary state of the CP (and of the DP universality class in general). Here we show explicitly (within the Gaussian approximation -though the conclusion is expected to be valid also beyond the approximation) that only the homogeneous fluctuation mode q = 0 is, at criticality, responsible for such a breaking, as in the case of systems with detailed balance (see, e.g, [13,20,27,30]). Indeed, let us generalize equation (15) to modes with q = 0:…”
Section: The Gaussian Approximationmentioning
confidence: 65%
See 3 more Smart Citations
“…As explained in subsection 2.1, Ξ −1 = 0 is a signal of the breaking of the RR symmetry characterizing the non-equilibrium stationary state of the CP (and of the DP universality class in general). Here we show explicitly (within the Gaussian approximation -though the conclusion is expected to be valid also beyond the approximation) that only the homogeneous fluctuation mode q = 0 is, at criticality, responsible for such a breaking, as in the case of systems with detailed balance (see, e.g, [13,20,27,30]). Indeed, let us generalize equation (15) to modes with q = 0:…”
Section: The Gaussian Approximationmentioning
confidence: 65%
“…Notice that we can use the O(ṽ 0 )-propagators to compute them up to O(ṽ). We first need the expressions for the following bubbles [27].) The result is The contribution I 2 is instead given by Its dimensional pole is properly removed by introducing the renormalized quantities according to equation (A.3), so that R R,q=0 = Z ψ R q=0 which gives indeed the expression in equation (30) forṽ =ṽ * R = ǫ/24 + O(ǫ 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scaling of two-time observables has been recently discussed in [9,10,11] and it was shown that for m 0 = 0 the universal scaling behaviour is different from the one found for m 0 = 0. An extension of LSI to non-equilibrium critical dynamics with non-vanishing initial magnetizations is an open problem to which to hope to return elsewhere.…”
mentioning
confidence: 99%